THE UTILITY OF STOP-BANG QUESTIONNAIRE IN SCREENING OSA IN PATIENTS WITH HEMORRHAGIC STROKE (The Research of Medical Science Review, 2025)
Objective: Study design: Cross-sectional study Place and duration: To determine the utility of STOP-BANG questionnaire in screening obstructive sleep apnea (OSA) in patients with hemorrhagic stroke. Neurology Department of Pak Emirates Military Hospital, Rawalpindi, for a duration of 6 months i.e. from July/2024 till Dec/2024 Patients and methods: After obtaining written informed consent, 220 patients who met the selection criteria were enrolled. All patients underwent assessment for OSA according to the STOP-BANG questionnaire within 24 hours of hemorrhagic stroke, followed by polysomnography (PSG) and presence of OSA was noted down and findings were subjected to statistical analysis. Results: The median (IQR) age of the patients was 50 (16) years. The median BMI of the patients was 26.3 (4.4) and the median NIHSS score was 5 (3). There were 123 (55.9%) males and 97 (44.1%) females in the study. OSA on STOP-BANG questionnaire was present in 108 (49.1%) patients. OSA on PSG was present in 97 (44.1%). STOP-BANG questionnaire was 95.9% sensitive, 87.8% specific and 91.4% accurate. Conclusion: For screening OSA in hemorrhagic stroke patients, STOP-BANG questionnaire had a high accuracy i.e. 91.4%